2022
DOI: 10.1108/ebhrm-07-2021-0148
|View full text |Cite
|
Sign up to set email alerts
|

Making Generation Y employees want to stick to their jobs: the roles of individualized consideration transformational leadership, occupational self-efficacy, and personal growth initiative

Abstract: PurposeBased on the self-determination and affective events theories, the current research examined the mediating role of occupational self-efficacy (OSE) between individualized consideration transformational leadership (ICTL) and affective commitment relationship. Furthermore, this study tests the moderating role of personal growth initiative on the relationship between ICTL and OSE.Design/methodology/approachTo examine the relationship, the authors carried out a time-lagged study spanning over four months fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…The results supported the idea that Generation Y workers who feel like they have a balanced life are more likely to feel committed to their jobs. This fits with what (Malik & Malik, 2022) says about work-life balance for Generation Y. He says that work-life balance should address both accomplishment and enjoyment and must include all four quadrants of work-life balance.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The results supported the idea that Generation Y workers who feel like they have a balanced life are more likely to feel committed to their jobs. This fits with what (Malik & Malik, 2022) says about work-life balance for Generation Y. He says that work-life balance should address both accomplishment and enjoyment and must include all four quadrants of work-life balance.…”
Section: Resultssupporting
confidence: 68%
“…This is because it was thought that commitment could be used to predict how employees would change over time. Aside from a possible drop in attrition, it appears that both the organization and the employees benefit from employees who are committed (Malik & Malik, 2022;Ye et al, 2022). In fact, it is thought that commitment not only makes people more productive and improves the quality of their work, but also makes them happier at work and less stressed.…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence suggests that personal growth initiatives are a positive career predictor for career adaptability, which can help newcomers cope with environmental demands in the workplace (Gregor et al, 2021). Research also demonstrated that personal growth initiative could positively and indirectly influence employees' occupational self‐efficacy by enhancing their perceptions of supportive leadership at work (Malik & Malik, 2022). To the best of our knowledge, however, there is a paucity of research examining the interaction between the working environment and personal growth initiative and its impact on job outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging empirical research on leadership and the millennial generation has inconsistently supported different types of leadership (e.g., empowering, transformational, LMX, Alif & Nastiti, 2022;Lee et al, 2022;Nelson, 2012;Shacklock & Brunetto, 2011). A variety of outcomes have been examined (e.g., turnover intention, well-being, creativity, commitment), typically without comparing generations (Alif & Nastiti, 2022;Anselmo-Witzel et al, 2020;Malik & Malik, 2022;Zhang & Zhao, 2021). Existing research tends to lack a generational rationale for its leadership focus, which is selected for its fit with the current business environment.…”
mentioning
confidence: 99%